2008
DOI: 10.1111/j.1471-0528.2008.01740.x
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review of the effects of aromatase inhibitors on pain associated with endometriosis

Abstract: Objective To assess the effects of aromatase inhibitors in women symptomatic of pain with endometriosis.Design A systematic review of published literature.Material and methods We conducted a comprehensive literature search to identify all the published observational and randomised studies evaluating the efficacy of aromatase inhibitors on pain associated with endometriosis. A combination of keywords was used to identify the maximum number of relevant citations in MEDLINE, EMBASE, CINAHL and the Cochrane Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(27 citation statements)
references
References 22 publications
(20 reference statements)
0
24
0
3
Order By: Relevance
“…Anastrozole is a type II aromatase inhibitor, which reversibly binds to the active enzyme site and dramatically decreases circulating estrogen levels (29). Its use in the treatment of endometriosis has been motivated by the overexpression of aromatase in endometriotic lesions and eutopic endometrium of women with endometriosis (2, 4), responsible for a local estrogen production and a resistance to GnRH analogues and oral progestins.…”
Section: Discussionmentioning
confidence: 99%
“…Anastrozole is a type II aromatase inhibitor, which reversibly binds to the active enzyme site and dramatically decreases circulating estrogen levels (29). Its use in the treatment of endometriosis has been motivated by the overexpression of aromatase in endometriotic lesions and eutopic endometrium of women with endometriosis (2, 4), responsible for a local estrogen production and a resistance to GnRH analogues and oral progestins.…”
Section: Discussionmentioning
confidence: 99%
“…5 Aromatase is a key enzyme in all estrogen synthesis, helping convert androstenedione and testosterone into estrone and estradiol, respectively, in a rate limiting step. 5,7,8 It is known that aromatase is expressed in high levels in endometriosis implants 5,7,8 and has been suggested that endometriosis lesions over-express aromatase, 6,8 thus securing their own estrogen supply, which is in turn suppressed by AI therapy. Takayama and colleagues were the first to report successfully treating refractory endometriosis after a hysterectomy and bilateral salpingo-oophorectomy in a postmenopausal woman with an AI in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…5 One randomized controlled trial showed that using AIs with GnRH analogues significantly improved pain scores compares to GnRH analogues alone, as both ovarian and extra-ovarian estrogen production was inhibited. 7 Another study showed that a GnRH analogue combined with anastrozole lengthened the pain free interval (35 vs 7.5% recurrence rate in the first 24 months). 6 Common side effects of AI therapy include headache, nausea, and diarrhea, but compared to GnRH agonists, hot flashes are milder and not as frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Les é tudes rapporté es tendent à suggé rer l'efficacité des anti-aromatases dans le traitement des endomé -trioses sé vè res. Bien qu'il n'y ait qu'une seule é tude randomisé e, de nombreux auteurs pensent que les anti-aromatases sont prometteurs [35]. En 2009, l'é quipe de Bedaiwi a é tudié le lé trozole associé à un traitement par agoniste de la GnRH chez neuf patientes atteintes d'endomé triose.…”
Section: Anti-aromatases Et Analogues De La Gnrhunclassified